2018
DOI: 10.7752/jpes.2018.01019
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The influence of tourism activities on residents' perceptions is indispensable for the development of these activities in the community. In particular, sports-tourism activities have increasingly influenced the development of community-based tourism in certain towns. The main objective of this study is to develop a valid scale to measure residents' perceptions of the impacts generated by sport tourism activities. The questionnaire has been developed and tested with a sample of 250 residents on the island of Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
1
14
0
2
Order By: Relevance
“…However, the studies that have used structural equation models and confirmatory factor analysis are scarcer and more recent (González- García, Añó, Parra & Calabuig, 2018;Kaplanidou et al, 2013;Kim et al, 2015;Kim & Walker, 2012;Lorde et al, 2011;Parra, González-García, Añó, & Ayora, 2016;Prayag et al, 2013). As Bollen (1989) points out, when there are well-developed theoretical frameworks and empirical evidence related to the area of research, confirmatory factor analysis is more appropriate when trying to develop a new tool.…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies that have used structural equation models and confirmatory factor analysis are scarcer and more recent (González- García, Añó, Parra & Calabuig, 2018;Kaplanidou et al, 2013;Kim et al, 2015;Kim & Walker, 2012;Lorde et al, 2011;Parra, González-García, Añó, & Ayora, 2016;Prayag et al, 2013). As Bollen (1989) points out, when there are well-developed theoretical frameworks and empirical evidence related to the area of research, confirmatory factor analysis is more appropriate when trying to develop a new tool.…”
Section: Discussionmentioning
confidence: 99%
“…Kapacitet regionalnog razvoja cikloturizma suočava se s izazovima poput "kratkotrajne prirode političkih ciklusa i prioriteta vlasti u ruralnim područjima, čvrstog oslanjanja na vodstvo i financiranje od regionalne ili državne vlasti, visoke stope promjene čelnika javnog sektora i sukoba između ugrađenog lokalnog parohijalizma i nametnutih regionalnih razvojnih struktura" (Carson, 2013). Lokalno stanovništvo jedna je od glavnih interesnih skupina u razvoju destinacijskog turizma (González-García et al, 2018) zbog čega su njihova podrška i angažman ključni čimbenici potpore stvaranju autentičnih iskustava sportskog turizma (Herbold, Thees i Philipp, 2020). Stanovnici bi stoga trebali biti više uključeni u planiranje i razvoj cikloturizma (Brščić, Lovrečić i Šugar, 2021), zajed-2 Za ovo je istraživanje važno objasniti razliku između biciklizma u slobodno vrijeme (eng.…”
Section: Cycling Tourism Local Stakeholders and Regional Developmentunclassified
“…The capacity of regional cycling tourism development may be challenged by "the short-lived nature of political cycles and government priorities in rural areas, an entrenched reliance on regional or state government leadership (and funding), high turnover rates of public sector leaders, and conflicts between embedded local parochialism and imposed regional development structures" (Carson, 2013). Residents are a key interest group in destination tourism development (González-García et al, 2018), and their endorsement and engagement are the critical support factors in creating authentic sport tourism 2 For the purpose of this research, a distinction between leisure cycling and utility (commuter) cycling should be noted. The latter implies functional rides with the aim of going to work, school or performing other regular duties.…”
Section: Cycling Tourism Local Stakeholders and Regional Developmentmentioning
confidence: 99%
“…Thus, gaining residents' support could emerge as a key task for managers responsible for tourism planning and development [35]. Regarding residents' perceptions, several authors [17,53,54] found that critical personal development is controlled for residents with positive perceptions of tourism development, who also support specific tourism development policies. This support can be enhanced by improving the standard of living and safety of residents and tourists, benefiting local residents economically, and encouraging a variety of cultural activities through the development of a range of tourism projects, such as seasonal cultural and folkloric events, inclusive sports and outdoor recreational facilities and activities, as well as meetings, incentives, conventions, and exhibitions [14,27,30,39].…”
Section: Introductionmentioning
confidence: 99%